Validating modelled data on major and trace element deposition in southern Germany using Sphagnum moss - Kempter, Heike; Krachler, Michael; Shotyk, William; Zaccone, Claudio (Atmospheric environment, 2017)
Sphagnum mosses were collected from four ombrotrophic bogs in two regions of southern Germany: Upper Bavaria (Oberbayern, OB) and the Northern Black Forest (Nordschwarzwald, NBF). Surfaces of Sphagnum carpets were marked with plastic mesh and, one year later, plant matter was harvested and productivity determined. Major and trace element concentrations (Ag, Al, As, Ba, Bi, Cd, Co, Cr, Cu, Fe, Mn, Mo, Pb, Rb, Sb, Sc, Sr, Th, Ti, Tl, U, V, Zn) were determined in acid digests using sector field ICP-MS. Up to 12 samples (40 × 40 cm) were collected per site, and 6-10 sites investigated per bog. Variation in element accumulation rates within a bog is mostly the result of the annual production rate of the Sphagnum mosses which masks not only the impact of site effects, such as microtopography and the presence of dwarf trees, but also local and regional conditions, including land use in the surrounding area, topography, etc. The difference in productivity between peat bogs results in distinctly higher element accumulation rates at the NBF bogs compared to those from OB for all studied elements. The comparison with the European Monitoring and Evaluation Program (EMEP; wet-only and total deposition) and Modelling of Air Pollutants and Ecosystem Impact (MAPESI; total deposition) data shows that accumulation rates obtained using Sphagnum are in the same range of published values for direct measurements of atmospheric deposition of As, Cd, Cu, Co, Pb, and V in both regions. The accordance is very dependent on how atmospheric deposition rates were obtained, as different models to calculate the deposition rates may yield different fluxes even for the same region. In future studies of atmospheric deposition of trace metals, both Sphagnum moss and deposition collectors have to be used on the same peat bog and results compared. Antimony, however, shows considerable discrepancy, because it is either under-estimated by Sphagnum moss or over-estimated by both atmospheric deposition models. Atmospheric deposition data obtained from sampling in open fields is unlikely to always perfectly match data obtained using living Sphagnum moss from bogs. In fact, plant uptake and biochemical utilization by living moss may affect accumulation rates of those elements that are essential for plant nutrition (macro and micronutrients), which is clearly seen in the data presented here for Mn, Fe and Zn. Furthermore, Sphagnum moss is a unique receptor, with its characteristic roughness and chemical complexity. These two aspects, combined with conditions found on the bog surface (variations in microtopography, shrubs, trees, wetness, snow cover, etc.), result in a unique type of interception and retention. Despite all these factors, the comparison with modelled data shows that Sphagnum moss is a good indicator of atmospheric deposition at least in a semi-quantitative manner and certainly reflects inputs to terrestrial ecosystems.
Gesehen am 04.08.2021